2021
DOI: 10.1017/s1049023x21000601
|View full text |Cite
|
Sign up to set email alerts
|

It’s Time to Talk to Prehospital Providers: Feedback Disparities among Ground-Based Emergency Medical Services Providers and its Impact on Job Satisfaction

Abstract: Objective: Performance feedback on clinical care and patient outcomes is a cornerstone of medical education, yet it remains lacking in the prehospital environment. Research seeking to establish the quantity of feedback provided to Emergency Medical Services (EMS) has been limited and studies focused on complimentary feedback or how feedback relates to EMS job satisfaction are lacking. The objectives of this study were to measure the frequency and nature of feedback received by EMS agencies and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Our survey revealed that only 6.2% of paramedics receive formal feedback on stroke, however, more than two-thirds of them think that hospital-directed feedback is crucial and would improve their future decision-making. These findings are in line with other studies, where formal feedback is noted as highly desirable for EMS staff members, yet not sufficient [ 8 , 10 , 12 , 13 , 14 , 19 , 28 , 29 , 30 ]. Previous studies have shown that hospital-directed feedback to EMS is associated with improved overall compliance with state protocols, increased hospital prenotification, and improved stroke timeliness metrics in patients with ischemic stroke [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our survey revealed that only 6.2% of paramedics receive formal feedback on stroke, however, more than two-thirds of them think that hospital-directed feedback is crucial and would improve their future decision-making. These findings are in line with other studies, where formal feedback is noted as highly desirable for EMS staff members, yet not sufficient [ 8 , 10 , 12 , 13 , 14 , 19 , 28 , 29 , 30 ]. Previous studies have shown that hospital-directed feedback to EMS is associated with improved overall compliance with state protocols, increased hospital prenotification, and improved stroke timeliness metrics in patients with ischemic stroke [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our survey revealed that only 6.2% of paramedics receive formal feedback on stroke, however, more than two-thirds of them think that hospital-directed feedback is crucial and would improve their future decision-making. These findings are in line with other studies, where formal feedback is noted as highly desirable for EMS staff members, yet not sufficient [8,10,[12][13][14]18,[27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…The non-interventional studies all reported that EMS professionals were dissatisfied with current feedback provision and desired more feedback, particularly patient outcome feedback 10–12 31 74 75. Concerns were that feedback was skewed towards the negative10 75 and only triggered by highly traumatic incidents,11 while EMS professionals desired routine, frequent and high-quality feedback 10–12. One UK study suggested that EMS professionals desired ‘pull’-type feedback, that is, initiated by individual clinicians, delivered electronically or involving staff mediators 11.…”
Section: Resultsmentioning
confidence: 99%
“…Potential social barriers were also highlighted, including how staff interact with and respond to feedback, especially within EMS culture where feedback may be perceived as linked to disciplinary action or being of questionable value 10 12. A reported ethical barrier was sharing of confidential patient details, especially for non-hospital-affiliated EMS agencies in the USA 10 75…”
Section: Resultsmentioning
confidence: 99%